2017
DOI: 10.1159/000453544
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes Derived from Human Pulmonary Artery Endothelial Cells Shift the Balance between Proliferation and Apoptosis of Smooth Muscle Cells

Abstract: Background: The overproliferation of pulmonary vascular cells is noted in pulmonary hypertension. The role of exosomes from pulmonary artery endothelial cells (PAEC) in the proliferation and apoptosis of pulmonary artery smooth muscle cells (PASMC) remains unclear. Methods: Exosomes were isolated and purified from the culture medium of PAEC using a commercial kit. Lipopolysaccharide (LPS), hypoxia, and hydrogen peroxide were utilized to induce PAEC injury. Coculture of PAEC and PASMC was conducted using Transw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
56
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(58 citation statements)
references
References 33 publications
0
56
1
Order By: Relevance
“…The marginal increase in the proliferation of SMCs on exposure to EVs from monotreatment group macrophages was in accordance with our previous in vitro as well as in vivo published findings where we demonstrated that a “dual hit” of HIV and cocaine significantly exacerbates smooth muscle hyperplasia and PAH phenotype compared to a “single hit” of either cocaine or viral proteins (9, 12). In recent years, the role of EVs in intercellular communication has been well established (53) in the pathogenesis of various diseases, including pulmonary hypertension (54, 55). Plasma exosomes from mice with monocrotaline-induced PAH were demonstrated to cause pulmonary hypertension in healthy mice and this effect was reversed by administering exosomes derived from mesenchymal stem cells (23).…”
Section: Discussionmentioning
confidence: 99%
“…The marginal increase in the proliferation of SMCs on exposure to EVs from monotreatment group macrophages was in accordance with our previous in vitro as well as in vivo published findings where we demonstrated that a “dual hit” of HIV and cocaine significantly exacerbates smooth muscle hyperplasia and PAH phenotype compared to a “single hit” of either cocaine or viral proteins (9, 12). In recent years, the role of EVs in intercellular communication has been well established (53) in the pathogenesis of various diseases, including pulmonary hypertension (54, 55). Plasma exosomes from mice with monocrotaline-induced PAH were demonstrated to cause pulmonary hypertension in healthy mice and this effect was reversed by administering exosomes derived from mesenchymal stem cells (23).…”
Section: Discussionmentioning
confidence: 99%
“…Extracellular vesicles derived from adipose MSCs have been shown to limit neointimal hyperplasia and in a study by Liu et al (2015) this was attributed to decreased macrophage infiltration, reduced expression of inflammatory cytokines and downregulation of the MAPK and PI3K signalling pathways. In another study, exosomes derived from pulmonary artery endothelial cells were shown to induce high levels of proliferation and exert anti‐apoptotic effects in pulmonary artery smooth muscle cells, contributing to vascular remodelling and the pathogenesis of pulmonary hypertension …”
Section: Discussionmentioning
confidence: 99%
“…In another study, exosomes derived from pulmonary artery endothelial cells were shown to induce high levels of proliferation and exert anti-apoptotic effects in pulmonary artery smooth muscle cells, contributing to vascular remodelling and the pathogenesis of pulmonary hypertension. 45 Accumulating evidence suggests that exosome-derived miRNAs may be involved in the regulation of various aspects of neointima formation via the modulation of target cell functions (eg proliferation and migration of VSMCs) and the resulting effects on vasculature homeostasis. 39,[46][47][48] It has been reported that MSC engraftment reduces vascular remodelling after coronary vessel balloon injury, this was demonstrated by a lower I/M, neointimal area and positive expression of PCNA in addition to enhanced re-endothelialisation after MSC transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, exosomes have gained interest as a source of biomarkers to assess the physiological condition of their cell of origin (de Jong et al, 2012). Both hypoxia and LPS have furthermore been shown to increase the release of exosomes from pulmonary artery ECs, which were involved in enhanced proliferation and resistance to apoptosis in pulmonary artery smooth muscle cells (Zhao et al, 2017). Additionally, ECs stimulated with transforming growth factor (TGF)-β1 induced shedding of VEGFR2-containing exosomes, which seemed to limit the effects of angiogenic stimuli on vascular sprouting (Jarad et al, 2017).…”
Section: Endothelial Extracellular Vesiclesmentioning
confidence: 99%